The neurolinguistic approach (NLA) to second or foreign language acquisition: An attempt to adapt this method to DELF exam preparation - Sgueglia, Valeria Emi (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
The neurolinguistic approach (NLA), a teaching method for French in particular, and for second or foreign language acquisition in general, transforms the conception of language learning processes and, therefore, teaching strategies. This note from the field provides an appraisal of the implementation of this method within a group of learners who, at the time, were demonstrating signs of lower self-confidence and engagement in their studies. It also provides an account of the author’s attempt to adapt the strategies of the NLA to the exam context and requirements of the Diplôme d’études en langue française (DELF), which corresponds to the first four levels of the Common European Framework of Reference for Languages.